Fun in Youth Rugby: A Mixed-Methods Study - Putt, Gary (Auckland University of Technology, 2021)
Research has identified fun as the central reason youth participate in sport and lack of fun as the primary reason they drop out (Crane & Temple, 2015; Visek et al., 2015). The role of fun in youth sport has gained growing attention from sport organisations. Sport New Zealand, New Zealand’s Government’s sport sector agency, has developed Balance is Better, an approach to youth sport emphasising fun and skill development (Sport New Zealand Ihi Aotearoa, 2021a). Understanding the factors that influence fun will inform policy and practice like Balance is Better and the design of Modified Sports. The purpose of this research was to contribute to what is known about fun in youth sport by examining the construct of fun in the context of rugby. Five research questions were investigated: (i) Why do youth play rugby?, (ii) What do youth find fun about rugby?, (iii) What are the important fun facilitators for youth playing rugby in New Zealand?, (iv) Can players be segmented based on how they perceive the importance of fun facilitators? If so, are these perception differences associated with differences in specific characteristics of a player’s Intrapersonal Profile? and (v) What are the important fun inhibitors for youth playing rugby in New Zealand? The study took a pragmatic mixed-methods approach to the study of fun. In the Qualitative Stage of the study, 13 boys, age 13-16, took part in semi-structured group interviews. From these interviews, Core Fun Elements of rugby were identified along with factors positively (Fun Facilitators) and negatively (Fun Inhibitors) influencing fun in New Zealand youth rugby. In the Quantitative Stage, a questionnaire was used to collect data on the importance of Fun Facilitators and Fun Inhibitors, along with demographic, psychographic and behavioural data associated with a player’s Intrapersonal Profile. A total of 527 boys aged 12-17 completed the questionnaire. These data were analysed to identify the importance of Fun Facilitators and Fun Inhibitors. T-test, ANOVA and correlation analyses were used to investigate how Intrapersonal Profile variables related to the player’s perceptions of Fun Facilitator importance. Cluster analysis was used to identify players that perceived Fun Facilitators importance similarly. The t-test, ANOVA and the cluster analysis results were then compared to characterise these groups further and relate Fun Facilitators perceived importance to aspects of an individual’s Intrapersonal Profile. The evidence generated from the study shows that fun is the number one reason male youth play rugby. Furthermore, four Core Fun Elements of youth rugby were identified: Physical Contact, Ball Play, Brotherhood, and Game Highlights. The Fun Facilitators of primary importance were found to be associated with: Positive team dynamics, Positive player attitudes, Learning and development, and Positive coaching. These fun facilitator themes align with key literature informing the present study (Visek et al., 2015). Important Fun Inhibitors were Bad or biased referees and Dirty players. A proposed model of Fun in Youth rugby is offered as a synthesis of the findings of this study. The model involves the six fun related themes (the four Core Fun Elements of rugby, Fun Facilitators, and Fun Inhibitors) and their relationship to increased or reduced fun while playing youth rugby. The proposed Fun in Youth Rugby model also integrates elements of the Hierarchical Model of Leisure Constraints (Crawford & Godbey, 1987, Crawford et al., 1991). This Hierarchical Model of Leisure Constraints outlines how an individual’s Intrapersonal Profile determines what an individual likes and therefore finds fun. Within the Fun in Youth Rugby model, a relationship is proposed between the six fun related themes and the Intrapersonal Profile of an individual. It is concluded that the alignment of a player's Intrapersonal Profile with the four thematic Core Fun Elements may have a significant role in determining if, and how much, an individual finds rugby fun. It is also suggested in the model that Fun Facilitators and Fun Inhibitors may enhance or reduce the fun experience of youth rugby players and that the importance of these Fun Facilitators, and potentially the Fun Inhibitors, may differ based on the player’s Intrapersonal Profile. These findings, model and conclusions have implications for sport delivery, design and modification. Firstly, care should be taken when altering the game of rugby in a way that impinges on four Core Fun Elements of youth rugby, since player’s fun and the attractiveness of the game to players may be affected. Secondly, to attract new players to a Modified Sport, due consideration needs to be given to the Core Fun Elements of the Modified Sport and how they may be perceived by the targeted players. Thirdly, to optimise a positive fun environment and experience for youth rugby players administrators need to focus on players, referees and coaches. The emotional and social competence of coaches is as important to player’s fun as the coach’s technical skills. Referees also have a key role to play in the fun experience of players. The availability of competent unbiased referees at all levels of youth rugby is very important to the overall fun experience of players. Lastly, a focus on developing players’ skills and attitudes, and eliminating ‘dirty play’, are other key factors in maximising the fun experience of youth rugby players.
Keywords: Fun; Rugby; Youth; Mixed-Methods; Intrapersonal Profile; Fun Facilitator; Fun Inhibitor